Management of Anterior Urethral Stricture: A Survey of Contemporary Practice of Iranian Urologists - Hosseini , Jalil; Khannejad, Samin; Attar, Armin; Goudarzikarim, Ali (Urology Journal, 2024)
Purpose: To evaluate Iranian urologists’ approach to urethral stricture and assess how often they select open urethroplasty over minimally invasive procedures. Material and methods: This cross-sectional observational study was conducted via www.survey.porsline.ir among members of the Iranian urologists’ community. The urologists were contacted via email and social media applications (e.g., WhatsApp, Telegram), and data, including their demographic information and years of practice, as well as questions related to their attitude towards the management of urethral stricture, were collected. Results: A total number of 376 patients were included in the current survey. The specialty of reconstructive urology was selected by less than 2% (n=5) as their field of interest. Only 6.64% (n=25) of the urologists stated that they received adequate training for management of urethral stricture. Only about 5% (n=19), believed that according to scientific resources, chose open urethroplasty as the initial management. Almost 94% (n=353) did not perform any urethroplasties during the past year and about 0.2% (n=2) performed more than 20 open urethroplasties. For diagnosing urethral stricture, almost 99% of them chose RUG+VCUG, 72% chose urethrocystoscopy, and 69% chose uroflowmetry in the third place. For evaluation of urethroplasty postoperative outcomes, 76% (n=269) used RUG+VCUG, 15% (n=56) used Rigid Cystoscopy, and 8% (n=29) used Flexible Cystoscopy, Conclusion: Iranian urologists prefer minimally invasive procedures for treating urethral stricture, similar to other countries. This lack of urologists’ interest in open urethroplasty is greatly due to poor training during the residency years and little experience with urethral strictures. Therefore, further considerations in order to improve urologists’ knowledge and expertise for management of urethral stricture is recommended.